Quality of human-computer interaction : results of a national usability survey of hospital-IT in Germany - Bundschuh, Bettina B.; Majeed, Raphael W.; Bürkle, Thomas; Kuhn, Klaus; Sax, Ulrich; Seggewies, Christof; Vosseler, Cornelia; Röhrig, Rainer; Justus Liebig University Giessen (My University, 2011)
Background: Due to the increasing functionality of medical information systems, it is hard to imagine day to day work in hospitals without IT support. Therefore, the design of dialogues between humans and information systems is one of the most important issues to be addressed in health care. This survey presents an analysis of the current quality level of human-computer interaction of healthcare-IT in German hospitals, focused on the users´ point of view.Methods: To evaluate the usability of clinical-IT according to the design principles of EN ISO 9241-10 the IsoMetrics Inventory, an assessment tool, was used. The focus of this paper has been put on suitability for task, training effort and conformity with user expectations, differentiated by information systems. Effectiveness has been evaluated with the focus on interoperability and functionality of different IT systems.Results: 4521 persons from 371 hospitals visited the start page of the study, while 1003 persons from 158 hospitals completed the questionnaire. The results show relevant variations between different information systems.Conclusions: Specialised information systems with defined functionality received better assessments than clinical information systems in general. This could be attributed to the improved customisation of these specialised systems for specific working environments. The results can be used as reference data for evaluation and benchmarking of human computer engineering in clinical health IT context for future studies.
Keywords: clinical healthcare IT; human-computer-interaction; germany; survey; ddc:610